MEMBANGUN PREFERENSI MERER MELALUI PEMAHAMAN TERHADAP KEPRIBADIAN KONSUMEN - ., Indraini (Manajemen dan Bisnis, 2002)
Consumer brand preference related to many factors which one is consumer personality. Under consumer behavior studies, personality means personel characteristic which determines and reflects how someone's respons to the environments. Personality theory which relevant to study the consumer behaviour are Freudian Theory, Neo Freudian Theory, and Trait Theory.A consumer tend to choose a specific product or brand which suitable which exiting aspects on his/her self personality. Beside that, they prefer to choose product or brand which can be used to enforce personality element for being confidence.The implementation of personality aspects weer focused on market segmenting that classified based on its personality. Market segmenting based on personality approach has advantage value on the product, because according that the company can promote its product based on its consumer personality which can build brand preference. Here, if the company can succesfully build brand preference, it will have impact on sales and consumer's loyalty.